Apixaban versus Warfarin in Patients with Left Ventricular (LV) Thrombus, a prospective randomized trial. (25th November 2020) - Alcalai, R; Rashad, R; Butnaru, A; Moravsky, G; Leibowitz, D
Abstract: Background: Patients with acute myocardial infarction (MI) have an elevated risk of stroke, mostly due to left ventricular (LV) thrombus formation, which typically occur within the first 2 weeks following an anterior MI. Currently the recommended management of LV thrombus after acute MI is anticoagulation with vitamin K antagonist. To date, there are no prospective data on the use of direct oral anticoagulants (DOACS) for stroke prevention in the setting of LV thrombus. Aim: To assess the efficacy of apixaban vs. warfarin in treating LV thrombus after MI. Methods: The study is a prospective, randomized, multi-center open label trial comparing apixaban (at a dose of 5 mg twice daily) with s.c enoxaparin 1mg/kg BID followed by dose-adjusted warfarin to achieve a target international normalized ratio (INR) of 2.0 to 3.0 for 3 months in patients with LV thrombus detected by echocardiography 3 to 14 days after acute MI. The primary outcome was the presence and size of LV thrombus 3 months after initiation of anticoagulation as assessed by 2D echocardiogram. Secondary outcomes were stroke or systemic embolism, major bleeding and death from any cause. Results: 25 patients have been enrolled to date in 3 medical centers, 13 were randomized to apixaban and 12 to warfarin. Mean age was 59.8±10.7 and 19 (76%) were males with no difference between the study groups. Mean LV thrombus size at enrollment was 24X15 mm in the apixaban group and 19X14 in the warfarin group (p=NS). After 3 months of treatment thrombus completely resolved in all patients in the warfarin group and in 12 of 13 in the apixaban group. In one patient in the apixaban group who had a very large thrombus of 40x20mm size upon enrollment the thrombus size was reduced significantly to 20x12 after 3 months. No death, stroke or systemic embolism was documented in either group. There were two patients with major bleeding in the warfarin group, one had sub-arachnoid hemorrhage after 2 months and anticoagulation was stopped, and another had GI bleeding after 1 month and was switched to enoxaparin. One patient in the warfarin group refused to continue the treatment after 3 weeks. No major bleeding events were recorded in the apixaban group and all patients completed 3 months of treatment. Conclusions: Our preliminary results indicate that apixaban is a safe and effective treatment for patients with LV thrombus post anterior wall MI. Funding Acknowledgement: Type of funding source: None